2020
DOI: 10.1371/journal.pone.0240557
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of metamorphopsia after reduced-fluence photodynamic therapy in patients with central serous chorioretinopathy with good baseline visual acuity

Abstract: This retrospective study was conducted to investigate the predictive factors associated with metamorphopsia after reduced-fluence photodynamic therapy (RFPDT) in patients with central serous chorioretinopathy (CSC) with good baseline visual acuity. A total of 36 eyes of 36 consecutive patients with resolved CSC after RFPDT and best-corrected visual acuity (BCVA) better than 1.0 (logarithm of the minimal angle of resolution (logMAR) 0) at baseline were examined. Metamorphopsia was measured using M-CHARTS at 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…In a Chinese cohort, none of the 7 SNPs examined in CFH were associated with 1-month outcomes after PDT in patients with CSCR 95. In contrast, in a Japanese cohort with a 12-month follow-up, the minor T allele of ARMS2 A69S was associated with poor response to PDT in patients with chronic CSCR 96…”
Section: Pharmacogenetics In Amd Pcv and Cscrmentioning
confidence: 81%
See 1 more Smart Citation
“…In a Chinese cohort, none of the 7 SNPs examined in CFH were associated with 1-month outcomes after PDT in patients with CSCR 95. In contrast, in a Japanese cohort with a 12-month follow-up, the minor T allele of ARMS2 A69S was associated with poor response to PDT in patients with chronic CSCR 96…”
Section: Pharmacogenetics In Amd Pcv and Cscrmentioning
confidence: 81%
“…95 In contrast, in a Japanese cohort with a 12month follow-up, the minor T allele of ARMS2 A69S was associated with poor response to PDT in patients with chronic CSCR. 96 In nAMD, pharmacogenetic studies on PDT have been focused on the ARMS2-HTRA1 and CFH genes, with variable results. In a Japanese cohort of wet AMD, the bestcorrected visual acuity (BCVA) 1 year after PDT was significantly increased in patients with HTRA1 rs11200638 GG as compared with patients with GA or AA.…”
Section: Pharmacogenetics In Amd Pcv and Cscrmentioning
confidence: 99%
“…At present, few studies have been published concerning the correlation between the duration of detachment and the severity of metamorphopsia in RRD [ 27 ]. Some studies reported that metamorphopsia correlated significantly with duration of symptoms in macular hole, central serous chorioretinopathy, and BRVO [ 17 , 28 , 29 ]. However, So et al found no correlation in ERM [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Central serous chorioretinopathy (CSC) causes retinal detachment, typically involving the macula, caused by the accumulation of subretinal fluid (SRF) accumulation [ 1 ]. Although CSC typically resolves spontaneously within 3–6 months [ 2 ] treatment administration should be considered to ensure the preservation of the quality of vision when SRF accumulation persists beyond this period.…”
Section: Introductionmentioning
confidence: 99%